HOAX DALAM TINJAUAN HADITS NABAWI - Ali Musri Semjan Putra (Sekolah Tinggi Dirasat Islamiyah Imam Syafi'i Jember, 2018)
Among the proofs of the greatness of God's power in the millennium is the emergence of various kinds of information media that are very helpful for ease in various matters. The convenience covers various fields of affairs, not just in the form of sharing information but has penetrated into the fields of business, education, da'wah and so on.Besides the many positive sides of social media, on the other hand social media is also a vehicle for various negative actions, such as hoaxes, fighting, sex trafficking, drug sales and so on. So this study tries to examine the nabawi hadiths relating to things that must be heeded in social media, specifically those related to hoaxes, with the induction approach using qualitative analysis. The purpose of the research is to provide insight to the community in using social media so that there is no violation of religious teachings or legislation when integrating on social media. As well as being a wrong solution in tackling and minimizing various forms of irregularities and violations that occur in the community in social media, both offenders in the form of crimes of intimidation, provocation, fraud, counterfeiting and so on, are spurred from hoax news.The conclusion of this study is that making or spreading hoaxes is an act that is strictly prohibited and prohibited in the nabawi hadiths which are the second source of law in Islamic law after the noble Qur'an. The culprit has the right to be punished in the world in a criminal manner or get a severe punishment in the hereafter, according to the effects and headlines of the lies he did.